PENGEMBANGAN MEDIA FLIPBOOK DIGITAL MATERI TEKS CERITA PADA PEMBELAJARAN BAHASA INDONESIA KELAS III SD - Holly Tambunan, Febbe; Marini, Arita; Hadi, Waluyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low reading literacy skills and the dominance of conventional teaching methods are persistent challenges in Indonesian language learning at the elementary school level. This study aimed to develop a digital flipbook learning medium for story text material in third-grade Indonesian language learning using the 4D development model (Define, Design, Develop, Disseminate). The development process was carried out through systematic literature analysis, instructional design, visual development using Canva and Heyzine Flipbook, expert validation, small-group trials, and limited dissemination. The developed medium consisted of 18 interactive pages integrating story text content, vocabulary exploration, fact-fiction identification, story structure analysis, QR Code-based interactive quizzes, writing practice, and learning reflection, all aligned with Phase B Learning Outcomes of Merdeka Curriculum. Validation results showed material expert rating at 98.33% (very valid), media expert at 96.67% (very valid), and student responses in the small-group trial at 90.63% (very valid). These findings confirm that the developed digital flipbook is highly feasible for use in third-grade Indonesian language learning. The novelty of this study lies in the development of an integrated digital flipbook specifically designed for story text material in third grade, incorporating differentiated learning principles aligned with Merdeka Curriculum Phase B and featuring a QR Code-based interactive quiz as an embedded formative assessment tool.